Pengaruh Net Profit Margin dan Current Ratio terhadap Harga Saham pada Perusahaan Food and Beverages - Silvia Vanesa; Ricky Evani (Jurnal Penelitian Ekonomi Akuntansi, 2023)
This research aims to test and analyze the influence of net profit margin (NPM) and current ratio (CR) on share prices in food and beverages companies listed on the Indonesia Stock Exchange (BEI) in the 2019-2022 period. The sampling method in this research uses a purposive sampling technique, using quantitative data types involving 108 data from 27 food and beverages companies listed on the Indonesia Stock Exchange. The data source in this research is secondary data obtained from financial reports, using a ratio scale. The analytical method used is multiple linear regression analysis. The results of this research show that net profit margin and current ratio influence stock prices. This study has limitations in processing data because the data tested before outliers is not normal, this is indicated that there is extreme data in several companies. Based on this, researchers can suggest further researchers using other sub-sectors such as the financial sector, mining sector, agricultural sector, and basic & chemical sectors, and other sectors besides the food and beverage sector.